Pantoea bathycoeliae sp. nov and Sodalis sp. are core gut microbiome symbionts of the two-spotted stink bug - Fourie, Arista; Venter, Stephanus N.; Slippers, Bernard; Fourie, Gerda (Frontiers in Microbiology, 2023)
Stink bug species (Pentatomoidea superfamily) have developed an interdependence with obligate bacterial gut symbionts in specialised midgut crypts (M4 sub region). Species of the Enterobacteriaceae family (predominantly Pantoea) are vertically transferred to their offspring and provide nutrients which cannot be obtained from plant sap food sources. However, the bacteria in the other gut compartments of stink bugs have rarely been investigated. The two-spotted stink bug, Bathycoelia distincta, is a serious pest of macadamias in South Africa. Nothing is currently known regarding its gut microbiome or how symbionts are transferred between insect generations. In this study the consistency of B. distincta gut bacteria across geographic locations and life stages was determined with 16S rRNA metabarcoding, considering both the M4 and other gut compartments. A novel Pantoea species was found to be the primary M4 gut symbiont and is vertically transferred to the offspring. The other gut compartments had a low bacterial diversity and genera varied between stink bug populations but a Sodalis species was prominent in all populations. Sequence data of the M4 compartment were used to produce high quality metagenome assembled genomes for the Pantoea and Sodalis species. Functional analyses suggested a similar role in nutrient provision for the host, yet also unique metabolites produced by each species. The Sodalis sp. also had additional traits, such as secretion systems, that likely allow it to establish in the host. The Pantoea species was described as Pantoea bathycoeliae sp. nov based on the rules of the SeqCode.